The Relationship Between the Use of KIA Books and Maternal Personal Hygiene with Stunting in the Working Area of the Kamaipura Health Center - Zefanya Tumewu; Lilik Sofiatus Solikhah; Ni Ketut Kariani (Jurnal Andaliman: Jurnal Gizi Pangan, Klinik dan Masyarakat, 2025)
Stunting is still a priority nutrition problem today. The Kamaipura Health Center is one of the health centers in Sigi Regency that is ranked first with the highest prevalence of stunting in 2023. Some of the factors that cause stunting are the low use of Maternal and Child Health (KIA) books and poor maternal personal hygiene. This study aims to analyze the relationship between the use of KIA books and maternal personal hygiene with stunting in children under five years aged 24-59 months in the working area of the Kamaipura Health Center. The research method used observational analytical design and a cross-sectional approach. The population was all toddlers aged 24-59 months. A sample of 112 respondents was selected using the simple random sampling method. Data were collected through interviews with structured. It is known that 56.2% of toddlers are stunted, 73.2% lack of knowledge, 52.7% do not use KIA books, and 37.5% do not have good personal hygiene. Stunted toddlers who have mothers with less knowledge are 69.5%, stunting toddlers who have mothers who do not use KIA books are 83.1%, and stunting toddlers who have poor personal hygiene are 95.2%. There was a significant relationship between knowledge (p<0.001), the use of KIA books (p<0.001), and personal hygiene (p<0.001) with stunting. There is a significant relationship between knowledge and stunting, the use of KIA books and stunting, and personal hygiene and stunting. There is a need for further research related to knowledge and the influence of nutrition education on the level of knowledge of mothers regarding the use of KIA books and personal hygiene using the pre post test method.